Evaluasi Kemampuan Lahan Di Kecamatan Tamban Di Kabupaten Barito Kuala - Putri Mayang Sari; Deasy Arisanty; Eva Alviawaty (JPG (Jurnal Pendidikan Geografi), 2016)
The title of this research is the Evaluation of Land Capability in Tamban Sub-District, Barito Kuala District. The purpose of this research is to find out the level of land capability in Tamban Sub-District Barito Kuala District.The population and sample of this research is equal which is land unit in Tamban Sub-District, Barito Kuala District with the total of sample of 22 land units. Land units are getting from overlay landform maps, soil type maps, the slope maps, and land use which obtain from satellite imagery and topography map.The result of this research shows for the matching method of the land in Tamban Sub-District, Barito Kuala District has two land capability classification that is IV Class and V Class. IV Class with the limiting factors are the erosion and drainage and V Class with the limiting factors are the erosion, drainage and permeability. The LCLP (Land Classification and Land Use Planning) Software in Tamban Sub-District Barito Kuala District has two land capability class which are IV Class with the limiting factors is drainage and V Class with the limiting factors is permeability.Keywords: Land Evaluation, land capability classification, and land capability class.